Capping agent‐free synthesis of surface engineered Pt nanocube for direct ammonia fuel cell. (26th June 2021) - Jin, Haneul; Lee, Sehyun; Sohn, Yeonsun; Lee, Soo‐Hyoung; Kim, Pil; Yoo, Sung Jong
Summary: Direct ammonia fuel cells (DAFCs), wherein the ammonia oxidation reaction (AOR) occurs at the anode and oxygen reduction at the cathode, are a promising clean energy production system using easily liquefied ammonia because they exhibit high energy density. However, only a few catalysts are, thus far, available for the AOR because of its sluggish six‐electron‐based reaction kinetics. Pt (100) is considered an optimal catalyst for the AOR; however, the synthesis of pristine Pt (100) is difficult because it requires the use of strong capping agents for faceting particles. Moreover, the capping agents block surface active sites, thereby deaccelerating electrochemical reactions. Herein, we report a novel synthetic method (hot separation) to achieve pristine Pt (100) by precisely controlling the formation kinetics of Pt nanocubes, wherein the further treatment for surface capping agent removal is not required. Hot separation prevents particle aggregation and overgrowth through the rapid separation of the Pt nanocubes and reaction solution and preserves the Pt (100) surface. Furthermore, the characterization of the pristine surface of Pt nanocubes was conducted to compare the properties of the Pt nanocubes with those of the particles prepared from conventional methods. The Pt nanocubes showed better mass activity toward the AOR and 2.3 times higher DAFC performance than those of commercial Pt. Abstract : Ammonia is promising energy sources in direct ammonia fuel cells but, catalysts for ammonia oxidation have not been fervently pursued because of their highly facet dependent performances. This communication reports a novel synthetic method of hot‐separation for Pt nanocubes, with pristine (100) surfaces, that does not require further purification. The Pt nanocubes show superb catalytic performances for ammonia oxidation.